(untitled) (Journal of Hama University, 2022)
Aim :This study aimed to evaluate the effect of sodium fluoride on cholesterol and Testosterone concentrations in male rabbits blood, in addition to measure the changes in the body ,Testicular and liver weights Materials and Methods The study was conducted on 21 male rabbits at age of six months, and for a period of two months in the breeding barn at the Faculty of Veterinary Medicine at the University of Hama, and it was divided into three groups (each group seven rabbits) were subjected to the same conditions of breeding in terms of ventilation, lighting, and food, and different in amount of sodium fluoride dose. Rabbits in the first group were dosed with 0.9% physiological saline serum in volume 1ml/kg while Rabbits in the second group were dosed with a solution of sodium fluoride at a concentration of 7.5 mg / kg ,the third group was dosed with a solution of sodium fluoride at a concentration of 15 mg / kg Rabbits were weighted at the beginning of the experiment and blood samples were taken from the auricle (after 1 months and two months of the start of the experiment), after which the serum was extracted, and the concentration of cholesterol and testosterone were measured then the rabbits were killed and weight of Testicular and liver were measured. Results: The results showed a significant increase in the concentration of cholesterol and a significant decrease in testosterone hormone in the groups that were dosed with sodium fluoride compared with the control group, as well as the weights of the experimental animals in the second and third groups dosed with sodium fluoride decreased, and an insignificant decrease was found in the liver weights of the second and third groups, while the decrease reached weight significant degree in the third group only. Conclusions: It has been concluded that the animals treated with sodium fluoride leads to harmful effect on them as it raises the concentration of cholesterol, decrease the testosterone hormone ,and the weight of body, liver ,and Testicular